February 16th, 2016, 04:57 AM | #1 |
Newbie Joined: Feb 2016 From: india Posts: 7 Thanks: 0 | 8w - 3 = 11
The question is "solve 8w - 3 = 11" help me out please. and another one is "solve 3(y - 4) = 9" |
February 16th, 2016, 04:59 AM | #2 |
Senior Member Joined: Nov 2010 From: Indonesia Posts: 2,001 Thanks: 132 Math Focus: Trigonometry |
8 - w = 11 8 - w - 8 = 11 - 8 -w = 3 If you don't know what to do after this then math is not for you. |
February 16th, 2016, 05:04 AM | #3 |
Newbie Joined: Feb 2016 From: india Posts: 7 Thanks: 0 | |
February 16th, 2016, 05:14 AM | #4 |
Senior Member Joined: Dec 2012 From: Hong Kong Posts: 853 Thanks: 311 Math Focus: Stochastic processes, statistical inference, data mining, computational linguistics | |
February 16th, 2016, 05:22 AM | #5 |
Senior Member Joined: Nov 2010 From: Indonesia Posts: 2,001 Thanks: 132 Math Focus: Trigonometry | |
February 16th, 2016, 05:56 AM | #6 |
Math Team Joined: Jul 2011 From: Texas Posts: 3,044 Thanks: 1627 | |
February 16th, 2016, 06:52 AM | #7 |
Senior Member Joined: Nov 2010 From: Indonesia Posts: 2,001 Thanks: 132 Math Focus: Trigonometry |
Oops, sorry. 8w - 3 = 11 8w - 3 + 3 = 11 + 3 8w = 14 Can you continue? |
February 16th, 2016, 11:57 AM | #8 |
Senior Member Joined: Dec 2015 From: holland Posts: 162 Thanks: 37 Math Focus: tetration |
8w-3=11 8w=11+3 w=14/8 =1+3/4 3(y-4)=9 y-4=3 y=7 Last edited by manus; February 16th, 2016 at 12:12 PM. Reason: forgot something |
February 16th, 2016, 12:12 PM | #9 |
Math Team Joined: Jan 2015 From: Alabama Posts: 3,264 Thanks: 902 |
You can, of course, reduce the fraction 14/8 to 7/4 and, if you wish, reduce that to the "mixed fraction" 1 and 3/4. r3v, all of these problems can be solved by "undoing" what has been done to the unknown value. In the first, 8- w= 11, we can think "on the right side, 8 has been added to -w. I can undo that by subtracting 8". And, of course, whatever we do to one side, we must do to the other. Doing that, we have -w= 11- 8= 3. Now, the only problem is that we have "-w" when we want "w". Thinking of that as "-1 times w", we undo it by dividing both sides by -1: -w/-1= 3/-1 so w= -3. In the second, 3(y- 4)= 9, we immediately see that the parentheses on the left side are multiplied by 3. We undo that by dividing both sides by 3: y- 4= 9/3= 3. Now, the only reason we do not have y by itself is that 4 is subtracted from it. We can undo that by adding 4 to both sides: y= 3+ 4= 7. |
February 16th, 2016, 04:31 PM | #10 |
Global Moderator Joined: Dec 2006 Posts: 21,036 Thanks: 2273 | |